Rubber wood sawdust fermentation by indigenous lignocellulolytic fungi for cellulase production - Ramli, Hunaidah (2017)
Microorganisms such as bacteria, fungal or yeast are often used for cellulase production using selected substrates via fermentation. However, relatively expensive cellulose powder as a main substrate hinders the industrial application of cellulase. Lignocellulose has been used as a substrate in producing cellulase as an alternative way towards more economic cost. The use of lignocellulolytic fungal in degradation of the lignocellulose are widely explored and studied due to its ability to produce both cellulase and ligninase. In this study, the potential of lignocellulolytic fungi in producing cellulase were investigated in solid-state fermentation of rubber wood sawdust. Four (4) indigenous fungal strains (Trichoderma aureoviride UPM 09, Fusarium equiseti UPM 09, Fusarium proliferatum UPM 09 and Aspergillus sp.) were screened for the best lignocellulolytic enzymes (cellulase and ligninase) producer. Solidstate fermentation of rubber wood sawdust was conducted in batch cultivation using modified Mandel’s medium in 250 ml shake-flask. A conventional method (one-factor-at-a-one-time) of optimization was applied to obtain maximum production of cellulase. Three parameters of medium optimization (types of nitrogen sources, peptone concentration and tween-80) and four parameters of cultural condition (initial medium pH, temperature, particle size and inoculum size) for cellulase production were investigated. From the experiments, only T. aureoviride UPM 09 and F. equiseti UPM 09 exhibit lignocellulolytic enzymes production. Hence, the two strains were selected for rubber wood sawdust fermentation. Throughout the fermentation, T. aureoviride UPM 09 showed the highest cellulase production of CMCase (12.99 U/g), FPase (1.57 U/g) and β-glucosidase (5.48 U/g). The optimum medium formulation and culture conditions for cellulase production were obtained using peptone as a sole nitrogen source at 2 g/L with addition of 1 % (v/v) tween-80 and initial medium pH of 5.0 at 25 ˚C. Two agar discs of fungal culture and 1.7 mm particle size of rubber wood sawdust were used as optimum inoculum and particles sizes. The production of cellulase was increased by 5.5-fold for CMCase (85.04 U/g), 1.9-fold for FPase (4.55 U/g) and 1.7-fold for β-glucosidase (14.92 U/g) using the optimized condition. Enzymatic hydrolysis of different pretreated rubber wood sawdust was carried out to evaluate the performance of crude cellulase activity obtained from the fermentation. The result showed that higher reducing sugar was produced (1.280 mg/ml) using chemical pretreated rubber wood sawdust as compared to biological pretreated rubber wood sawdust (0.577 mg/ml) and raw rubber wood sawdust (0.103 mg/ml). In conclusion, T. aureoviride UPM 09 is a high potential strain to be used in cellulase production. The cellulase production by T. aureoviride UPM 09 was greatly improved after optimization process which can be further studied using statistical approach.